Economic Rationale of Agricultural Development in Cold Desert Areas of Himachal Pradesh - Oberoi, R C (Annals of Arid Zone, 2016)
The data obtained through two stage stratified random sampling design from 65 farmers of cold desert of Spiti Valley revealed that the agriculture of cold desert area is mostly traditional, primitive and subsistent in nature. Improved technology was not found to have any significant impact in the study area. The optimum farm plans suggested that with the introduction of improved technology and reallocation of resources, as high as 50 per cent increase in farm income could be attained. The vast potential of agriculture in the study area remained untapped because of number of geographical, social and economic constraints. The major economic constraints responsible for non-adoption of improved technology were inadequate and untimely supply of farm inputs, smaller holdings, scarcity of capital, inadequate irrigation facilities and lack of adequate extension services in the study area. Once the constraints responsible for poor agricultural development are removed, there lies a wide scope of improving the tribal agriculture. The study also suggested that keeping in view the non-economic constraints there is a need to follow the psycho-social approach for the agricultural development of the cold deserts.